Epidemiology of dialysis-treated end-stage kidney disease in adults in Libya - Alashek, Wiam Abdulaziz. (2013)
Background: The extent and the distribution of end stage kidney disease (ESKD) in Libya have not been reported despite provision of dialysis over 4 decades. The aim of this thesis is to develop the first comprehensive description of the epidemiology of dialysis-treated ESKD in adults in Libya as well as to assess the outcomes of this treatment.